Violence against women: The perspective of academic women - (:unkn) unknown (BIOMED CENTRAL LTD, 2010)
Background: Opinion surveys about potential causes of violence against women (VAW) are uncommon. This study explores academic women's opinions about VAW and the ways of reducing violence. Methods: Quantitative and qualitative methods were used in this descriptive study. One hundred-and-fifteen academicians participated in the study from two universities. A questionnaire was used regarding the definition and the causes of VAW, the risk groups and opinions about the solutions. Additionally, two authors interviewed 8 academicians from universities other than that of the interviewing author. Results: Academicians discussed the problem from the perspective of gender-based violence rather than family violence. The majority of the participants stated that nonworking women of low socioeconomic status are most at risk for VAW. They indicated that psychological violence is more prevalent against educated women, whilst physical violence is more likely to occur against uneducated and nonworking women. Perpetrator related factors were the most frequently stated causes of VAW. Thirty-five percent of the academicians defined themselves as at risk of some act of VAW. Recommendations for actions against violence were empowerment of women, increasing the educational levels in the society, and legal measures. Conclusions: Academic women introduced an ecological approach for the explanation of VAW by stressing the importance of taking into account the global context of the occurrence of VAW. Similar studies with various community members -including men- will help to define targeted interventions.
Keywords: INTIMATE PARTNER VIOLENCE